Comparative effectiveness of liquid and freeze-dried vaccines for oral vaccination of dogs against rabies - Z. D. Yershebulov; A. T. Zhunushov; Zh. T. Amanova (Ветеринария сегодня)
Currently, vaccination is the main measure to combat rabies in domestic and wild animals. Inactivated and live vaccines are used for this purpose. Oral vaccines for wild carnivores contain live attenuated rabies viruses in liquid or freeze-dried form, which are packaged inside edible baits. Since there are no consistent data showing advantages of liquid and freeze-dried oral products for vaccine-induced immunity against rabies in animals, we compared effectiveness of these rabies vaccines produced from rabies virus strain VRC-RZ2. Immunogenicity was tested in mongrel dogs aged 3 months and older that are seronegative for rabies virus antigens. The animals were randomly divided into three groups: two experimental and one control group. Group One was fed a block-type bait containing a blister with liquid virus-containing suspension, Group Two was given a block-type bait containing a gelatin capsule with freeze-dried virus suspension. On Day 21 post vaccination, blood samples were taken from all the animals and the obtained sera were examined in virus neutralization test to measure virus neutralizing antibodies titers. The level of the immune response against rabies in the vaccinated dogs was assessed by intracerebral infection of animals with virulent rabies virus strain CVS. The carried out research demonstrated that both groups of the vaccinated dogs had approximately the same titers of virus neutralizing antibodies that ranged from 3.25 to 4.33 log2. The virus neutralizing antibodies observed in the immunized dogs ensured good protection from virulent CVS strain. All animals of the control group died after infection demonstrating clinical signs of paralytic rabies. The results obtained show that both forms of the oral rabies vaccines are effective.